Low-sulphate water sample preparation for LSC detection of 35S avoiding sulphate precipitation - Schubert, Michael; Kopitz, Jürgen; Knöller, Kay (Journal of environmental radioactivity, 2020)
Information about groundwater residence times is essential for evaluating appropriate groundwater abstraction rates and aquifer vulnerabilities and hence for sustainable groundwater management in general. Naturally occurring radionuclides are suitable tools for related investigations. While the applicability of several long-lived radionuclides for the investigation of long-term processes has been demonstrated frequently, residence times of less than one year are only scarcely discussed in the literature. That is due to the rather small number of applicable radionuclides that show adequately short half-lives. A promising approach for investigating sub-yearly residence times applies radioactive sulphur. 35S is continuously produced in the upper atmosphere from where it is transferred with the rain to the groundwater. As soon as the water enters the subsurface its 35S activity concentration decreases with an 87.4 day half-life. This makes 35S suitable for investigating sub-yearly groundwater residence times. However, the low 35S activities in natural waters require sulphate pre-concentration for 35S detection by means of liquid scintillation counting (LSC). That is usually done by sulphate extraction from large water samples with an anion-exchange resin (Amberlite IRA400, Cl-form), elution from the resin with NaCl, and precipitation as BaSO4. Our study aimed at optimizing the standard sample preparation procedure by avoiding the laborious precipitation step. We suggest (i) sulphate extraction using the exchange resin Amberlite IRA67 (OH-form), (ii) elution with ammonium hydroxide, (iii) evaporation of the eluate and (iv) dissolving the resulting dry precipitate in 2 ml H2O. In contrast to the standard approach our method results in a final sample solution of low ionic strength, which allows applying the water miscible scintillation cocktail Hionic-Fluor®. Since Hionic-Fluor accepts only aqueous solutions of low ionic strength the approach is applicable for waters with high 35S/32SO42− ratios, i.e., low total sulphate sample loads (e.g. rainwater).